Two-Stage Synthesis of 3-(Perfluoroalkyl)-Substituted Vinyldiazocarbonyl Compounds and Their Nonfluorinated Counterparts: A Comparative Study - Supurgibekov, Murat B.; Prakash, G. K. Surya; Nikolaev, Valerij A. (Synthesis, 2013)
Two approaches for the synthesis of fluorinated (F) and nonfluorinated (H) 4-(alkoxycarbonyl)-substituted cis- and trans-vinyldiazocarbonyl compounds with substituents of variable stereoelectronic nature (H, Me, Ph, CF3, OTBS) at the C-3 atom of the vinyl double bond from the relevant 1,3-dicarbonyl compounds were compared: a pathway using the Wittig reaction followed by a diazo transfer reaction was most efficient for the synthesis of the H-vinyldiazocarbonyl compounds (total yields of up to 60%), while the yields of their F-analogues under similar conditions did not exceed 16–37%. An approach via diazo transfer followed by the Wittig reaction, in contrast, is more effective for the preparation of F-vinyldiazocarbonyl compounds (total yields 37–69%). The configuration of the resulting F- and H-vinyldiazocarbonyl compounds is evidently controlled by the steric bulk of the substituent at the C-3 atom of the vinyl double bond and, in addition, depends on the specific synthetic pathway.
Keywords: (perfluoroalkyl)-containing vinyldiazocarbonyl compounds; diazo transfer; Wittig reaction; 1,3-diketones